2012
DOI: 10.1089/scd.2011.0722
|View full text |Cite
|
Sign up to set email alerts
|

Same or Not the Same? Comparison of Adipose Tissue-Derived Versus Bone Marrow-Derived Mesenchymal Stem and Stromal Cells

Abstract: Mesenchymal stem/stromal cells (MSCs) comprise a heterogeneous population of cells with multilineage differentiation potential, the ability to modulate oxidative stress, and secrete various cytokines and growth factors that can have immunomodulatory, angiogenic, anti-inflammatory and anti-apoptotic effects. Recent data indicate that these paracrine factors may play a key role in MSC-mediated effects in modulating various acute and chronic pathological conditions. MSCs are found in virtually all organs of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
558
0
31

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(616 citation statements)
references
References 278 publications
8
558
0
31
Order By: Relevance
“…This finding is consistent with those of numerous studies corroborating this phenomenon in in vitro and animal studies [1,5,6,8,33]. Strioga et al [33] reported that this may be attributable to fewer in vivo cell division events for aMSCs, resulting in longer telomere lengths and greater reserve capacity. aMSCs seem to be buffered from physiologic insult as residents of a quiescent tissue, whereas bmMSCs are subject to a dynamic environment constantly adapting to homeostatic derangements.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with those of numerous studies corroborating this phenomenon in in vitro and animal studies [1,5,6,8,33]. Strioga et al [33] reported that this may be attributable to fewer in vivo cell division events for aMSCs, resulting in longer telomere lengths and greater reserve capacity. aMSCs seem to be buffered from physiologic insult as residents of a quiescent tissue, whereas bmMSCs are subject to a dynamic environment constantly adapting to homeostatic derangements.…”
Section: Discussionsupporting
confidence: 90%
“…To carry out a comprehensive comparative analysis, we selected whole MSC populations from bone marrow and adipose tissue (bmMSCs and aMSCs, respectively), which share several biological features but also demonstrate peculiarities in their differentiation potential, transcriptome, proteome, and immunomodulation function. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Так, количество МСК, которые можно выделить из жировой ткани, в 100-1000 раз пре-вышает их количество, содержащееся в эквива-лентном объеме костного мозга [2]. Кроме того, выделенные из жировой ткани МСК генетически более стабильны в течение длительного срока культивирования, отличаются более низким ко-эффициентом старения и высокой пролифера-тивной активностью [3,31]. Жировая ткань может быть легко получена при проведении стандартной процедуры липосакции под местной анестезией, а методы липотрансфера широко используются в современной пластической хирургии.…”
Section: клеточная терапия остеоартрозаunclassified
“…Жировая ткань может быть легко получена при проведении стандартной процедуры липосакции под местной анестезией, а методы липотрансфера широко используются в современной пластической хирургии. Кроме того, стромально-васкулярная фракция (СВФ) липо-аспирата является богатым источником не толь-ко МСК, но и других типов клеток, участвующих в регенерации тканей, например, предшествен-ников эндотелиальных клеток, преадипоци-тов, фибробластов, тучных клеток, макрофагов, Т-и В-лимфоцитов [13,31]. Клетки СВФ оказыва-ют противовоспалительный и иммуномодулирую-щий эффекты; кроме того, содержащиеся в СВФ МСК способны дифференцироваться в клетки со-единительной ткани, включая хрящи, сухожилия и связки [32].…”
Section: клеточная терапия остеоартрозаunclassified